2009
DOI: 10.1080/17429140802323338
|View full text |Cite
|
Sign up to set email alerts
|

Promotive effects of phosphorus on crop productivity, enzyme activities, anthraquinone and sennoside content inCassia toraL. – a medicinal herb

Abstract: The plants of Cassia tora L. were grown in pots containing soil, supplied with five levels of phosphorus: 0 (Control), 0.1, 0.2, 0.3 and 0.4 g P per kg soil. The fresh and dry weights, number of leaves and leaf-area per plant were recorded. The leaves were analyzed for inorganic elements, such as nitrogen, phosphorus, potassium and calcium. Physiological and biochemical attributes including chlorophyll and carotenoid content, nitrate reductase activity, carbonic anhydrase activity, net photosynthetic rate, sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
2
2
0
Order By: Relevance
“…As per Figure 4, the enhancement in leaf-N, -P and -K content could be due to phosphorus-encouraged absorption of additional amount of nutrients from the soil as noted by Graciano, Goya, Frangi, and Guiamet (2006) with regard to Eucalyptus grandis. Our results in this regard are consistent with those of earlier studies on different medicinal crops (Khan, Samiullah, Afaq, & Afridi, 2000;Naeem & Khan, 2005Naeem, Masroor, et al (2009). GA 3 application improved the seed yield in fenugreek (Table 2).…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…As per Figure 4, the enhancement in leaf-N, -P and -K content could be due to phosphorus-encouraged absorption of additional amount of nutrients from the soil as noted by Graciano, Goya, Frangi, and Guiamet (2006) with regard to Eucalyptus grandis. Our results in this regard are consistent with those of earlier studies on different medicinal crops (Khan, Samiullah, Afaq, & Afridi, 2000;Naeem & Khan, 2005Naeem, Masroor, et al (2009). GA 3 application improved the seed yield in fenugreek (Table 2).…”
Section: Discussionsupporting
confidence: 96%
“…Our results are in agreement with other studies conducted by different workers in different plants like Zea mays (Sinha, Srinivatsa, & Tripathi, 1993), Glycine max (Zhao, Lin, Shi, & Chang, 1995) and Schefflera arboricola L. (Salehi Sardoei, Roein, Shahadadi, Sadeghi, & Mokhtari, 2014). The enhancement of the photosynthetic pigments due to P application has earlier been reported by and Naeem, Masroor, et al (2009).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Additionally, the increase in leaf-NR activity with increasing ISA concentration in the present investigation is in agreement with the findings reported by Naeem et al (2011) in the case of Mentha arvensis L. Similarly, Aftab et al (2011) reported ISA-mediated increase in overall plant growth and other yield and quality parameters in Artemisia annua L. Regarding the positive effect of P on leaf-NR activity, our results find support from the studies on maize (de Magalhaes et al, 1998) and beans (Gniazdowaska et al, 1999), which confirm enhanced assimilation of leaf-NO 3 − content due to P application. In conformity with our results, enhancement in leaf-NR activity with phosphorus application has been reported by several workers in different medicinal and aromatic plants such as Cassia tora (Naeem and Khan, 2005), Cyamopsis tetragonoloba L. (Burman et al, 2007), Senna occidentalis L. (Naeem and Khan, 2009), Cassia tora L. (Naeem et al, 2009a) and Cassia sophera L. (Naeem et al, 2009b).…”
Section: Nitrate Reductase (Nr) Activitysupporting
confidence: 94%